2010
DOI: 10.1148/radiol.09090596
|View full text |Cite
|
Sign up to set email alerts
|

Patellar Cartilage: T2 Values and Morphologic Abnormalities at 3.0-T MR Imaging in Relation to Physical Activity in Asymptomatic Subjects from the Osteoarthritis Initiative

Abstract: Purpose:To study the interrelationship between patella cartilage T2 relaxation time, other knee abnormalities, and physical activity levels in asymptomatic subjects from the Osteoarthritis Initiative (OAI) incidence cohort. Materials and Methods:The study had institutional review board approval and was HIPAA compliant. One hundred twenty subjects from the OAI without knee pain (age, 45-55 years) and with risk factors for knee osteoarthritis (OA) were studied by using knee radiographs, 3.0-T knee magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
5
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 126 publications
(140 citation statements)
references
References 52 publications
7
127
5
1
Order By: Relevance
“…The UCSF-modified WORMS grading [19,20] was used to semi-quantitatively assess articular cartilage, bone marrow lesions (BML), and subchondral cysts of the patellofemoral joint at baseline and 48-month follow-up. Cartilage was graded on an incremental scale from 0 (normal cartilage thickness and signal) to 6 (diffuse full-thickness loss in more than 75% of the region) and BML and subchondral cysts were graded on an incremental scale from 0 to 3 according to their size.…”
Section: Magnetic Resonance Imaging and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The UCSF-modified WORMS grading [19,20] was used to semi-quantitatively assess articular cartilage, bone marrow lesions (BML), and subchondral cysts of the patellofemoral joint at baseline and 48-month follow-up. Cartilage was graded on an incremental scale from 0 (normal cartilage thickness and signal) to 6 (diffuse full-thickness loss in more than 75% of the region) and BML and subchondral cysts were graded on an incremental scale from 0 to 3 according to their size.…”
Section: Magnetic Resonance Imaging and Analysismentioning
confidence: 99%
“…To the best of our knowledge, associations of SPFP imaging findings with patellofemoral joint degeneration and clinical worsening have not yet been assessed in a longitudinal analysis. Therefore, the aims of this study were first, to analyze the association of MRI findings of SPFPs with progression of patellofemoral OA, as assessed by the modified Whole-Organ Magnetic Resonance Imaging Score (WORMS) [19,20] over 48 months, and second, to evaluate associations between SPFP abnormalities and clinical outcome over 48 months.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects with mild and severe OA had significantly higher cartilage T 2 values than those who were healthy. A study of the Osteoarthritis Initiative patient cohort [36] showed a link between heightened T 2 values of patellar cartilage and knee abnormalities. It has, however, been suggested that explicit interpretation of changes in T 2 should be made with care, owing to the number of competing biological and mechanical effects that influence T 2 [1].…”
Section: Mri Of Cartilagementioning
confidence: 99%
“…T2 haritaları kıkırdaktaki normal alanları dejenerasyon alanlarından ayırt etmek için kullanılabilir olmasına rağmen, orta ve ciddi hastalığı ayırmada yardımcı olabilecek T2 harita ile osteoartrit arasında doğru orantılı bir ilişki yoktur [57]. Ayrıca fiziksel aktivite- [58]. T2 haritalama tekniğinin kıkırdak onarı-mının zamanla takip edilmesinde kullanılabilir olduğu gösterilmiş olup çoğu klinik MR sisteminde kolayca uygulanabilir hal almıştır [59].…”
Section: T2 Haritalama Tekniğiunclassified